Peran Bank Syariah: Menuju Perekonomian Masyarakat Madani - Dini Maulana Lestari; M Roif Muntaha; Immawan Azhar BA (Mabsya: Jurnal Manajemen Bisnis Syariah, 2019)
Islamic banks are present in the community as financial institutions whose activities are based on the principles of Islamic law for the benefit of the people. This study aims to determine the strategic role of Islamic Banks as financial service institutions, the importance of the existence of Islamic Banks and Islamic-based markets and financial instruments in them. In its development, Islamic banks have a role as institutions that turn on public funds, channel funds to the public, transfer assets, liquidity, reallocation of income and transactions. In the Indonesian economic system, the existence of Islamic Banks is important as an alternative solution to the problem of conflict between bank interest and usury. Islamic financial markets and instruments provide a free society of interest and follow a different set of principles. Distribution of profit/ loss according to evidence of participation in the management fund. The division of rental income in the form of musharaka.